Analysis of First Successful Transmission in a Buffered CSMA/CD - C.Y, Pee,; A.H, Pooi, (Malaysian Journal of Science, 2002)
The buffered non-persistent CSMA/CD-type LAN proposed by Boyanov and Ruskov is a Markovian LAN model. The characteristics of the network were derived analytically by Lee and Pee. In this paper, we derive the distribution of the time required to get the first successful transmission for the model.